Sistem Hematologi dan Imunologi: Sinergi Kompleks dalam Pertahanan Tubuh - Mutiara Syaharani Dewi; Nabila Putri Sari Dewi; Maya Dila Aprilia; Luqyana Shifa Andaini; Levina Arum Hindiani; KM. Lathifah; Liss Dyah Dewi Arini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The haematological and immunological systems have traditionally been viewed as separate entities, but they operate through a fundamental two-way synergy that is essential for the body's defence. This article aims to map the complex mechanisms linking these two systems through a systematic literature review. This review identifies three main pillars of synergy. First, haematopoiesis serves as the foundation that produces all immune cells, a process itself dynamically regulated by immune signals. Second, inflammation is a coordinated response in which cytokines direct the recruitment of haematological cells (neutrophils, monocytes) to the site of injury. Third, immunothrombosis represents an advanced synergy in which platelet and neutrophil interactions activate coagulation to trap pathogens. This review concludes that dysregulation in one system, such as chronic inflammation, can directly drive pathology in the other systems, including thrombosis and haematological malignancies, highlighting the importance of integrated therapeutic approaches.